2013
DOI: 10.1016/j.ejso.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of older rectal cancer patients is not impaired by a permanent stoma

Abstract: Older patients with a stoma have comparable HRQL to older patients without a stoma or the normative population, indicating the feasibility of a permanent stoma for elderly patients with a low situated rectal carcinoma. The negative impact of treatment on sexual functioning as found in the current study calls for further attention to alleviate this problem in sexually active patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…Similar results were found in other studies with longitudinal QOL measurements [27][28][29] and confirmed by a systematic review of 23 studies regarding the changes in physical-and role functioning after colorectal cancer treatment [30]. Also, worse postoperative physical functioning in older patients compared to younger patients was described previously [7,[32][33][34][35][36][37]. Our results may add that older patients still report poor physical-, social-, and role functioning up to one year after diagnosis compared to their pretreatment level and compared to the reference population, indicating slow recovery or permanently affected functioning.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results were found in other studies with longitudinal QOL measurements [27][28][29] and confirmed by a systematic review of 23 studies regarding the changes in physical-and role functioning after colorectal cancer treatment [30]. Also, worse postoperative physical functioning in older patients compared to younger patients was described previously [7,[32][33][34][35][36][37]. Our results may add that older patients still report poor physical-, social-, and role functioning up to one year after diagnosis compared to their pretreatment level and compared to the reference population, indicating slow recovery or permanently affected functioning.…”
Section: Discussionsupporting
confidence: 77%
“…5,11,[27][28][29][30] our study showed that the patients <70 years undergoing tme surgery had significantly better postoperative sexual function and less male sexual dysfunction compared with patients ≥70 years, regardless of treatment. 5,11,[27][28][29][30] our study showed that the patients <70 years undergoing tme surgery had significantly better postoperative sexual function and less male sexual dysfunction compared with patients ≥70 years, regardless of treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, our findings related to sex and time since surgery do not directly contradict comparative studies using disease-specific HRQOL measures that have found, for example, that women and survivors with ostomies have worse HRQOL outcomes in certain domains or that the effect of an ostomy on HRQOL is attenuated by increased age. 9,28 …”
Section: Discussionmentioning
confidence: 99%